2021
DOI: 10.1016/j.omtn.2021.08.034
|View full text |Cite
|
Sign up to set email alerts
|

circ_PTN contributes to -cisplatin resistance in glioblastoma via PI3K/AKT signaling through the miR-542-3p/PIK3R3 pathway

Abstract: Glioblastoma has been identified as the most common and aggressive primary brain tumor in adults. Recently, it has been found that cisplatin (DDP) treatment is a common chemotherapeutic method for GBM patients. circ_PTN (ID number: hsa_circ_0003949) is a newly found circular (circRNA) which has been proved to be highly expressed in GBM cells, while its role in GBM remains unclear. Therefore, our study focused on investigating the role of circ_PTN in the DDP resistance of GBM cells. The expression of circ_PTN i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Previous studies have shown that the PI3K-AKT pathway plays an important role in DDP resistance [ 29–32 ]. We speculate dwhether PTPRZ1 was involved in DDP resistance of OC by regulating the PI3K-AKT pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the PI3K-AKT pathway plays an important role in DDP resistance [ 29–32 ]. We speculate dwhether PTPRZ1 was involved in DDP resistance of OC by regulating the PI3K-AKT pathway.…”
Section: Discussionmentioning
confidence: 99%
“…3a, the Mo/AlN/Mo film stacks are sputtered on a silicon-on-insulator (SOI) wafer. AlN film, deposited at 300 °C by DC-pulse reactive magnetron sputtering, achieves average stress within +/− 50 MPa and a stress range within 200 MPa based on our previous work 46,47 . The top patterned Mo electrode is typically designed at a size of 65-70% of the cavity diameter in order to effectively collect the charge of AlN piezoelectric layer.…”
Section: Pmut Device and Systemmentioning
confidence: 75%
“…Recently, circRNAs have become more attention as new prognostic or therapeutic targets for tumors. CircRNAs were found to be differentially expressed in GBM [25][26][27][28][29][30][31][32]. In addition, previous research showed that circRNA was regulated by HIF-1α under hypoxia condition.…”
Section: Discussionmentioning
confidence: 99%